Studi Literatur: Relevansi Diamond Fraud Theory Dalam Menilai Perilaku Fraud - Michael Revelin Ervan Septian; Tri Ratnawati (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
The aim of this research is to determine the relevance of diamond fraud theory in assessing fraudulent behavior. This research is a qualitative descriptive study using literature. The results of this research indicate that diamond fraud theory is not relevant in assessing fraudulent behavior. At this time, the fraud hexagon theory is appropriate and relevant in assessing fraudulent behavior.